Hubungan Perilaku Bidan dengan Mutu Pelayanan Prima Kebidanan di Rumah Sakit X Boyolali - Ratih Kumala Dewi; Evita Aurilia Nardina; Wahyuningsih Wahyuningsih (Journal of Health Management Research, 2026)
Background: Midwifery services are a key determinant in improving maternal and neonatal health outcomes. Midwives’ behaviors, including empathy, communication, professionalism, and responsiveness, have been shown to influence the quality of nursing and midwifery care perceived by patients. At Hospital X Boyolali, internal data revealed persistent complaints regarding insufficient empathy and delayed responsiveness, despite compliance with technical medical standards. This highlights the need to examine the contribution of midwives’ behaviors to the quality of midwifery care. Aims: This study aimed to analyze the relationship between midwives’ behaviors and the quality of midwifery care as perceived by patients in Hospital X Boyolali. Methods: A quantitative study with a cross-sectional analytic design was conducted involving 70 midwives selected through proportional random sampling. Data were collected using a structured questionnaire consisting of 15 items on midwives’ behaviors and 20 items on quality of care. Instrument reliability was confirmed with a Cronbach’s alpha of 0.872. Data were analyzed using the chi-square test with a 5% significance level. Results: Most midwives demonstrated good behaviors in empathy (64.3%), communication (60.0%), professionalism (68.6%), and responsiveness (57.1%). Patients’ perceptions of care quality were predominantly rated as high, with reliability showing the highest proportion (71.4%). The chi-square test indicated a significant association between midwives’ behaviors and the quality of midwifery care (p = 0.002). Conclusion: Midwives’ behaviors play a crucial role in determining the quality of midwifery services. Efforts to improve service quality should prioritize strengthening empathetic, communicative, and professional behaviors through continuous soft skills training and professional development programs.